Not for ourselves alone [videorecording (DVD)] : the story of Elizabeth Cady Stanton & Susan B. Anthony - Burns, Ken, 1953-; Kellerman, Sally; Gilbert, Ronnie; Harris, Julie, 1925-2013 (PBS Home Video ; Distributed by Paramount Home Entertainment, 2004)
Presents the history of women's suffrage in the United States through the dramatic, often turbulent friendship of Elizabeth Cady Stanton and Susan Anthony. Part 1 covers the years from their youth up to the establishment of the National Woman Suffrage Association in 1868. Part 2 spans the period from 1868 to the passage in 1919 of the 19th amendment to the Constitution which gave women the vote.